2014
DOI: 10.1038/nrm3854
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microRNA function in somatic stem cell proliferation and differentiation

Abstract: microRNAs (miRNAs) are important modulators of development. Owing to their ability to simultaneously silence hundreds of target genes, they have key roles in large-scale transcriptomic changes that occur during cell fate transitions. In somatic stem and progenitor cells — such as those involved in myogenesis, haematopoiesis, skin and neural development — miRNA function is carefully regulated to promote and stabilize cell fate choice. miRNAs are integrated within networks that form both positive and negative fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
238
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(241 citation statements)
references
References 105 publications
2
238
0
1
Order By: Relevance
“…Mice-Loss of microRNAs could result in up-or down-regulation of mRNAs and the corresponding proteins depending on cell type and developmental status and for other reasons (75)(76)(77)(78). To test, how loss of DICER-dependent miRNAs affects gonadotropin synthesis in pituitaries of male mice, we first quantified gonadotropin subunit mRNAs by real time qPCR assays.…”
Section: Loss Of Dicer In Gonadotropes Results In Suppressed Gonadotrmentioning
confidence: 99%
“…Mice-Loss of microRNAs could result in up-or down-regulation of mRNAs and the corresponding proteins depending on cell type and developmental status and for other reasons (75)(76)(77)(78). To test, how loss of DICER-dependent miRNAs affects gonadotropin synthesis in pituitaries of male mice, we first quantified gonadotropin subunit mRNAs by real time qPCR assays.…”
Section: Loss Of Dicer In Gonadotropes Results In Suppressed Gonadotrmentioning
confidence: 99%
“…In the last decades, miRNAs have been postulated as important regulatory molecules in many cellular and developmental pathways (15,16). Numerous studies have focused on the assessment of miRNA expression and have shown considerable changes in their expression profiles in various diseases (17)(18)(19)(20), although the most remarkable changes have been observed in cancer (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Mature miRNAs are small noncoding RNAs that interact with their targets by partial base pairing with complementary sequences commonly found within the 3′ untranslated region (3′ UTR) of the target mRNA. In the majority of cases, miRNA binding inhibits translation and/or destabilizes the target mRNA (20). Similar to lin-28, let-7 was initially identified in C. elegans as a heterochronic gene (10,21).…”
mentioning
confidence: 99%